2014
DOI: 10.1177/0095798414537939
|View full text |Cite
|
Sign up to set email alerts
|

Predictor and Moderator Effects of Ego Resilience and Mindfulness on the Relationship Between Academic Stress and Psychological Well-Being in a Sample of Ghanaian College Students

Abstract: This study examined the predictor and moderator effects of ego resilience and mindfulness on the relationship between academic stress and psychological well-being in a sample of Ghanaian college students (N = 431). The results indicated that academic stress was positively associated with both anxiety and depression and that mindfulness and ego resilience were both negatively associated with anxiety and depression. Mindfulness buffered the positive relationship between academic stress and depression but not anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 31 publications
6
32
0
1
Order By: Relevance
“…As expected, stress was positively associated with symptoms of anxiety, and depression. This is consistent with previous studies of anxiety (Byrne et al, 2007;Cole et al, 2014;McLaughlin and Hatzenbuehler, 2009) and depression (Bouma et al, 2008;Cole et al, 2014;Grant et al, 2004b;Tram and Cole, 2000). When resilience was taken into account as a mediator it was found that higher levels of stress were associated with lower levels of resilience, which in turn was positively associated with anxiety and depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As expected, stress was positively associated with symptoms of anxiety, and depression. This is consistent with previous studies of anxiety (Byrne et al, 2007;Cole et al, 2014;McLaughlin and Hatzenbuehler, 2009) and depression (Bouma et al, 2008;Cole et al, 2014;Grant et al, 2004b;Tram and Cole, 2000). When resilience was taken into account as a mediator it was found that higher levels of stress were associated with lower levels of resilience, which in turn was positively associated with anxiety and depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Mindfulness moderated the relationship between stress and depression but not anxiety while ego resilience moderated the relationship between stress and anxiety but not depression. Simple slope analysis showed the effect of stress on depression was significantly higher for low levels of mindfulness than for high levels of mindfulness while the effect of stress on anxiety was significantly higher for low levels of ego resilience than for high levels of ego resilience (Cole et al, 2014).…”
Section: Diatheses -Stress Perspectivementioning
confidence: 91%
See 1 more Smart Citation
“…Mindfulness interventions have been applied to relieve caregiver stress in working with individuals with autism (Ruiz-Robledillo, Sariñana-González, Pérez-Blasco, González-Bono, & Moya-Albiol, 2015), to increase well-being in college students (Cole et al, 2015), to facilitate emotional regulation (Fogarty, Lu, Sollers, Krivoschekov, Booth, & Consedine, 2015). Relevant to this study, the effects of mindfulness have been used in regards to traumatic experience.…”
Section: Evidence Of This Relationship Was Seen Inmentioning
confidence: 99%
“…A student population is relevant to the current study, because previous studies have shown that students go through a variety of traumatic events, including bereavement (Burke, 2010) and elevated stress (Hindman, Glass, Arnkoff, & Maron, 2015). Due to these types of concerns, students are more vulnerable to mental health concerns (American Psychiatric Association, 2013), and as a result of academic stress are more susceptible to depression and anxiety (Cole et al, 2015). Students will often have been exposed to a variety of arduous life experiences, academic or otherwise, that may be perceived as difficult or traumatic.…”
Section: The Present Studymentioning
confidence: 99%